An action research case study: digital equity and educational inclusion during an emergent COVID-19 divide. Issue 1 (22nd January 2021) - Pittman, Joyce; Severino, Lori; DeCarlo-Tecce, Mary Jean; Kiosoglous, Cameron
Abstract : Purpose: This paper aims to share responses from current literature, a small case study about perceptions and practices of the school of education faculty toward multicultural and educational issues concerning the rapid rise in online environments during coronavirus (COVID-19) experiences and just-in-time strategies for addressing digital equity and educational inclusion in K-16 online educational settings. Design/methodology/approach: This is a conceptual paper that emerged from an action research case study. The study included four faculty in an urban school of education. The faculty participants were asked to provide examples of educational inclusion strategies used during transitioning their courses and advising to online environments in a Research I university. Faculty included one educational leadership, one sports management, one special education and one teacher education professor. Central issues explored practices related to language, technology access, curriculum design and technological competencies and assessment. A driving question was: How do institutions, schools or educators provide learning opportunities to support digital equity and inclusive education practice to maintain and strengthen relationships and core practices of multicultural education during a time of physical distancing during COVID-19? And what are the experiences, barriers, successes? Findings: Research-based transformative knowledge, real situations and practical resources for considering inclusive education curriculum concepts were found that are connecting educators, teachers, learners and communities during this time of crisis. Research limitations/implications: Methodological limitations that influenced the research design include conducting research in a totally virtual environment, small sample size, lack of diversity in curriculum content and one research site. The data collection was limited to written responses from the faculty participants. This action research study took place in a time frame limited by COVID-19 conditions during a four-month period. Practical implications: In theory and practice, this new online movement suggests learners, teachers, educators and leaders are gaining experience and knowledge about resources and strategies for using new technologies, assessments and flexible curriculum as powerful tools for building language, curriculum and social-cultural communication bonds across generations and including special needs populations. Such new and emerging strategies could be used to bridge gaps in a time of distancing to support inclusive and equitable learning environments in education to minimize the effects of an emergent COVID-19 digital divide. Social learning culture as constructed, performed and captured in patterns of cooperation among faculties shows the world becoming more open and less restricted by borders. In conclusion, an emerging new conceptual framework is presented in Figure 2 to support action planning to bridge the digital equity access and learning gaps created by COVID-19. Social implications: It is in times of strife and difficulty that problems and issues become exacerbated. While some educators easily adapted and took on the challenges of online learning, others needed time for learning and mourning (literally and figuratively). The issues of equity and access have become even more apparent as this paper takes inventory of intersections between multicultural education, special education, sports education and K-16 education overall. This is an excellent time to reflect on how education can address the cultural, economic and social barriers that impact student learning globally for all learners. Originality/value: The brief collective case study reports educational experiences during a time of crisis that stimulates creative and innovative approaches to creating inclusive and equitable online learning environments to address diverse learning needs. The various and often contrasting educator responses from faculty facing digital and educational challenges present ideas that might be applicable in the global learning environment beyond the COVID-19 pandemic.